GIS application in Land-level spatial planning: With special reference to the spatial planning register for Saxony-Anhalt - Bauch, Peter; Schauerte Lüke, Norbert (Raumforschung und Raumordnung | Spatial Research and Planning, 2001)
This article considers spatial planning registers as a suitable vehicle for demonstrating the introduction of a GIS for the purposes of comprehensive spatial planning atLand (state) level. It starts with an explanation of the spatial planning registers now required to be maintained by all of Germany’sLänder (except for the city-states) and goes on to describe in detail the kinds of modifications which will have to be made to such registers as they come to be converted into digital form. Taking for purposes of demonstration a GIS application currently in use in a number of German states, the authors outline the requirements such systems need to meet and propose possible technical solutions using standard software. The final section looks in greater detail at the necessary modifications to spatial planning registers associated with conversion to digital form, including possible changes to the way registers are organised and new ways of using the data.